ANALISIS NILAI-NILAI KARAKTER MATERI KERAGAMAN SUKU BANGSA PADA BUKU SISWA KELAS IV TEMA INDAHNYA KERAGAMAN DI NEGERIKU - Feby Triani, - (2020)
This research is motivated by the problem of low character values and the importance of teaching materials applied to learning activities in shaping and developing the character of students in grade IV of elementary school. The good and bad character of a person that is build by the attitude and behavior of the individual. The character of every human being can occur because they always continue to follow the habits that are carried out in everyday life. In the implementation of learning activities, the teaching material has been compiled into textbooks or textbooks that serve to facilitate teachers and students in the process of learning activities. Ethnic diversity is one of the teaching materials that contain character values for students. The purpose of this research is to identify the material values of ethnic diversity in the theme book of fourth grade students "Indahnya Keragaman Negeriku". This study used a content analysis research method with a qualitative approach. The research object used was the thematic book of the fourth grade students of the second semester with the theme "Indahnya Keragaman Negeriku", the 2017 revision. The results of the research have shown that the analysis of the character values of the material on ethnic diversity in the fourth grade student book on the theme "Indahnya Keragaman Negeriku". It is in sub-theme 1, namely "Keragaman Suku Bangsa dan Agama di Negeriku". In the material of ethnic diversity, almost all character values are found. ethnic diversity material contains character values. Character values that are often found are the foster love of the motherland, tolerance and curiosity. Meanwhile, the character values that were not found were religious, honest, and social care.